Structure of Customs Tariffs Worldwide and in the European Community - Carsten Weerth (Global Trade and Customs Journal, 2008)
The Nomenclature that is governed by the Convention on the Harmonized Commodity Description and Coding System (Harmonized System Convention, Brussels, 14 June 1983) has resulted in an adjustment of many nomenclatures used worldwide for statistical and customs classifi cation because nomenclatures that are based on the HS nomenclature are accepted in more than 200 countries and economic regions – more than 98 percent of world trade is classified according to the HS nomenclature. However, only the first six digits are uniform (HS-6), and further subdivisions are allowed if the structure of the HS nomenclature is not altered. Basically, most customs tariffs worldwide are uniform and the statistical data are comparable, which is important for economic research and comparability of economic data. However, the European Community (EC) applys a Common Customs Tariff (CCT) that is not uniform, because the EC combined statistical and customs nomenclature (so called Combined Nomenclature – CN) allows a further subdivision of the Integrated Customs Tariff (TARIC, HS-6 + 4) by an 11th digit if there is a national purpose in one of the EC Member States.
Additional information: Self-archiving of author's post-print (accepted paper) for scientific use only on personal page in RePec (e.g. https://authors.repec.org) according to publishers policies as documented on SHERPA/ROMEO database under URL: http://www.sherpa.ac.uk/romeo/issn/1569-755X/en//. Copyright-holder is Kluwer Law International.
Keywords: K33; K34; 330; Customs Law; World Customs Organization; International Law; Trade; Customs Classification